Manipulating plant community composition to steer efficient N‐cycling in intensively managed grasslands. Issue 1 (11th November 2020) - Abalos, Diego; De Deyn, Gerlinde B.; Philippot, Laurent; Oram, Natalie J.; Oudová, Barbora; Pantelis, Ioannis; Clark, Callum; Fiorini, Andrea; Bru, David; Mariscal‐Sancho, Ignacio; van Groenigen, Jan Willem
Abstract: Minimizing nitrogen (N) losses and increasing plant N uptake in agroecosystems is a major global challenge. Ecological concepts from (semi)natural grasslands suggest that manipulating plant community composition using plant species with different traits may represent a promising opportunity to face this challenge. Here, we translate these trait‐based concepts to agricultural systems in a field experiment, aiming to reveal the main determinants of how plant community composition regulates N‐cycling in intensively managed grasslands. We focused on key N pools (plant N from soil and from biological N‐fixation, soil mineral N and N2 O emissions) as well as on biological drivers of N‐cycling in soil (abundance of N‐cycling microbial communities, earthworm populations and arbuscular mycorrhizal fungi), using three common grass and one legume species in monoculture, two‐ and four‐species mixtures. We hypothesized that: (a) plant species mixtures increase plant N uptake, reduce soil mineral N concentrations and N2 O emissions and promote the abundance of biological N‐cyclers; (b) legume presence stimulates N pools, fluxes and biological N‐cycling activity, (c) but in combination with a grass with acquisitive traits, more N is retained in the plant community, while N2 O emissions are reduced. We found that mixtures increased plant N and lowered the soil mineral N pool compared to monocultures. However, plant species identity played an overarching role: Legume presence increased N2 O emissions, plant N pools, soil mineral N and the abundance of N‐cycling microbes and earthworms. Combining the legume with a grass with low leaf dry matter content and high root length density (and with high root biomass) reduced the higher soil mineral N and N2 O emissions induced by the legume, while harnessing positive effects on plant N pools and biological N‐fixation. Synthesis and applications . Our results show the potential of plant community composition to steer N‐cycling in fertilized agroecosystems, paving the way for a more biologically based agriculture. Legumes will play a crucial role, but selecting an optimum companion species is key for the sustainability of the agroecosystem. Abstract : Our results show the potential of plant community composition to steer N‐cycling in fertilized agroecosystems, paving the way for a more biologically based agriculture. Legumes will play a crucial role, but selecting an optimum companion species is key for the sustainability of the agroecosystem.